A paradigm shift from upstream reservoir to downstream/coastal reservoirs management in Malaysia to meet SDG6 - Chong, Tan Yew (IAHR, 2020)
Water is the core of sustainable development. Water scarcity affects more than 40% of the global population and this percentage is projected to rise. Malaysia, despite having abundant annual rainfall, experiences water stress in major cities. In order to achieve Sustainable Development Goal 6 (SDG6), the Malaysian government recognizes the need to harvest water using alternative methods. As a result, Malaysia has recently seen a paradigm shift in water resources development works from traditional upstream reservoirs to downstream reservoirs.